PERBANDINGAN METODE SEASONAL ARIMA DAN METODE EXPONENTIAL SMOOTHING DALAM MERAMALKAN KUNJUNGAN WISATAWAN MANCANEGARA KE BALI - CAHYANTARI, NI PUTU AYU DEWI; SUMARJAYA, I WAYAN; WIDANA, I NYOMAN (E-Jurnal Matematika, 2021)
Tourism is one of the main sectors in increasing a country's economy. For this reason, an estimate of tourist visits to Bali is needed so that it can be used as a benchmark for development and development in the tourism sector. Forecasting the number of foreign tourists coming to Bali using the Seasonal ARIMA method produces an MSE value of 1,250,276,526. While the Winter's Exponential Smoothing method obtained 1,291,150,258. The results of the forecast for the number of foreign tourists coming to Bali in 2020 using the SARIMA method are 588,980, 653,740, 659,817 (January-March 2020).